Hubungan Antara Manajemen Diri DenganKedisiplinan Kerja Pada Karyawan - Nuvitasari, Alviana; , Drs. Mohammad Amir, M.Si (2016)
One of success indicators in a company in developing their business is the presence of high disciplin in their workers. Work disciplin can be influenced by many factors, one of them is self-management. This research aimed at knowing: a) the correlation between self-management and work disciplin; b) the levels of selfmanagement and work discipline; c) The effective contributions of self-management on work discipline. The hypothesis proposed was: there was a positive correlation between self-management and work disciplin. The higher of the self-management, the higher of the work discipline was. In contrary, the lower of the self-management, the lower of the work discipline was.The subjects of research were workers of Fishing and Marine Department of Kendal Regency as many as 45 people. The method of data collection used the scales of self-management and work discipline. The results of data analysis used correlation of product moment obtained the coefficient of correlation as much as 0.629; p = 0.000 (p < 0.01) that meant that there was a very positively significant correlation between self-management and work discipline. The higher of the self-management, the higher of the work discipline was, in contrary, the lower of the self-management, the lower of the work discipline was. The contribution of self-management on work discipline was as much as 39.6%, therefore, there was still 60.4 of the factors influencing the work discipline outside the selfmanagement variable. Based on the results of the categorization counting, it was known that the selfmanagement of the research subjects was categorized as high, showed by the empirical mean as much as 109.42 and hypothetical mean as much as 95. The work discipline of the research subjects was categorized as high, showed by the empirical mean as much as 139.07 and hypothetical mean as much as 120. Keywords: self-management, work discipline.